2004
DOI: 10.1111/j.1365-2621.2004.tb09920.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Cooking Properties of Ground Pork Patties as Affected by Various Fat Levels

Abstract: Ground pork patties were processed from pork hams to achieve fat levels of 5%, 10%, 15%, 20%, and 25%. Each patty was cooked in a microwave oven to 75°C from a thawed state. As fat levels increased, cooking time decreased. Total cooking loss and drip loss were highest for 25% fat patties and lowest for 5% fat patties. High-fat patties (20% and 25%) had greater reductions in dia than did 5% to 15% fat patties, but had less change in patty thickness. Shear force values decreased as fat levels increased. Visual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
25
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 25 publications
(26 reference statements)
14
25
5
Order By: Relevance
“…Even though SL‐containing patties had lower PMD, it did not resulted in higher a * values. In the present study, PMD values were slightly lower than those recorded by Jeong and others (2004) for microwave‐cooked pork patties. This may be due to differences in cooking equipment and endpoint temperatures.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Even though SL‐containing patties had lower PMD, it did not resulted in higher a * values. In the present study, PMD values were slightly lower than those recorded by Jeong and others (2004) for microwave‐cooked pork patties. This may be due to differences in cooking equipment and endpoint temperatures.…”
Section: Resultscontrasting
confidence: 86%
“…The majority of studies on cooking of meat and meat products were carried out with conventional cooking methods. However, there is little information in the literature (Jeong and others 2004) concerning emulsion‐type meat patties, especially chicken patties cooked by microwave energy. Keeping in mind the beneficial effects of SL and CL, this study was designed to develop a new healthier, reduced‐sodium and calcium‐enriched cooked chicken patties and to evaluate the changes in physicochemical properties, cooking characteristics, microbial growth, oxidative stability, and sensory properties of microwave‐cooked chicken patties formulated with SL, CL, or SL+CL over a 28‐d refrigerated storage period.…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods of preparing meat patties for consumption such as deep fat frying, single-sided and double-sided contact frying, microwaving, infrared radiation and convection heating (Erdogdu et al, 2005;Jeong et al, 2004). The main differences among these various cooking techniques are the temperature on the surface of the meat, the temperature profile through the meat and the method of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that increase in fat content results in decrease in dielectric constant and loss factor (Gunasekaran and others 2005). However, fat accelerates the microwave heating rate and increases the maximum temperature achieved (Jeong and others 2004; Ryynänen and others 2004), probably due to the low specific heat compared to water (Schiffmann 1993). The thermal properties of foods affect the heat gradient from zones with absorbed microwave energy to colder spots.…”
Section: Introductionmentioning
confidence: 99%